Practice variation across consent templates for biobank research. a survey of German biobanks - Hirschberg, Irene; Knüppel, Hannes; Strech, Daniel (Frontiers in Genetics, 2013)
Introduction: Informed, voluntary, and valid consent from biomaterial donors is a precondi-tion for biobank research. Valid consent protects donors’ rights and helps maintain public trust in biobank research. Harmonisation of consent procedures in biobank research is needed, because of the widely shared vision on national and international networking of biobanks in-cluding data and sample sharing. So far, no study has assessed and compared the content of current consent forms for biobank research. The objective of this study was to perform a con-tent analysis of consent forms in German biobanks. Methods: Based on 10 guidelines for biomedical research, we developed an assessment ma-trix with 41 content issues that are potentially relevant for consent forms in biobank research. This assessment matrix was applied in a thematic text analysis to 30 consent documents of German biobanks identified via the German Biobank Registry in July 2012. Results: Coverage of the 41 items in the assessed consent forms varied widely. For example, the items “Right to withdraw consent (without disadvantage)”, “Policy for genetic infor-mation / consent to genetic analyses” and “International cooperation / transborder use” were addressed in 97%, 40% and 23% of all 30 consent forms respectively. The number of items covered by a single consent form ranged from 9 to 36 (22% to 88% out of 41 items). Discussion: Our findings serve as a starting point to reflect upon the spectrum of consent is-sues that must be addressed in biobank research. The findings show that the majority of con-sent forms for German biobanks, if not all, should be improved and harmonised to better sup-port an informed and balanced choice of potential donors and to facilitate networking of bi-obanks. Best practice models for consent forms in biobank research should be developed and biobank operators need to be more aware of relevant consent issues.